Analisis Investasi dan Sensitivitas Unit Usaha Pembiayaan Syariah menuju Spin Off (Studi Kasus: Adira Finance) - Lita Wulandari; Hermanto Siregar; Hendri Tanjung (AL-MUZARA'AH, 2017)
The purpose of this study to determine the level of investment feasibility and sensitivity level of sharia financing business unit in the process towards spin off. The investment feasibility analysis is carried out in two schemes: the funding scheme is fully borne by the sharia unit of Adira Finance and the joint financing scheme of funding of units to be financed. Sensitivity analysis is calculated by the scenario of decreasing the number of units financed and the scenario of increasing the financing composition of joint financing. Parameters to be measured in these two analyzes are: Net Present Value (NPV), Benefit Cost Ratio (B/C ratio), Internal Rate of Return (IRR) and Break Even Point (BEP). Based on the calculation of investment analysis, the sharia business unit is not eligible to be separated into sharia unit business if all funding is charged to sharia business unit. While the results of sensitivity analysis calculations obtained that motor finance products more vulnerable to changes in scenarios than car finance products.